An analysis of aeolian dust in climate models. Issue 16 (18th August 2014) - Evan, Amato T.; Flamant, Cyrille; Fiedler, Stephanie; Doherty, Owen
Abstract Aeolian dust is a key aspect of the climate system. Dust can modify the Earth's energy budget, provide long‐range transport of nutrients, and influence land surface processes via erosion. Consequently, effective modeling of the climate system, particularly at regional scales, requires a reasonably accurate representation of dust emission, transport, and deposition. Here we evaluate African dust in 23 state‐of‐the‐art global climate models used in the Fifth Assessment Report of the Intergovernmental Panel on Climate Change. We find that all models fail to reproduce basic aspects of dust emission and transport over the second half of the twentieth century. The models systematically underestimate dust emission, transport, and optical depth, and year‐to‐year changes in these properties bear little resemblance to observations. These findings cast doubt on the ability of these models to simulate the regional climate and the response of African dust to future climate change.